Characterization of SrAl₂O₄:Eu²⁺,Dy³⁺ nano thin films prepared by pulsed laser deposition - Nsimama, Patrick Damson (University of the Free State, 2010)
English: Thin films of SrAl2O4:Eu2+,Dy3+ phosphor were deposited on silicon (Si (100)) substrates using a 248 nm KrF pulsed laser. Deposition parameters, namely; substrate temperature, pulse repetition rate, number of laser pulses, base pressure and the working atmosphere were varied during the film deposition processes. Atomic force microscopy (AFM), Scanning electron microscopy (SEM), X-ray Diffraction (XRD), energy dispersive x-ray spectroscopy (EDS), and the fluorescence spectrophotometry were used to characterize the thin films. The surface characterization was done by using Auger electron spectroscopy (AES) combined with CL spectroscopy and X-ray photoelectron spectroscopy (XPS). PL data were collected in air at room temperature using a 325 nm He-Cd laser PL system and the UV Xenon lamp Cary Eclipse fluorescence spectrophotometer. The particle morphologies, surface topographies and photoluminescence (PL) properties were varying with the deposition parameters. Rougher film surfaces gave better PL properties. The optimum substrate temperature for SrAl2O4:Eu2+,Dy3+ films with intense PL emission was in the 350-400o C range. SrAl2O4:Eu2+,Dy3+ thin films ablated using a higher number of pulses gave superior PL properties to those deposited at lower number of pulses. As-deposited films prepared in the gas atmospheres gave AFM images with well defined particles and better PL properties than those deposited in vacuum. The average particle sizes for films deposited in gas atmospheres were ranging from 25 nm to 40 nm. The results from XRD and HRTEM showed that the as-deposited SrAl2O4:Eu2+,Dy3+ thin films were amorphous. Upon annealing at 800o in vacuum for 2 hours, the PL of the films deposited in the gas atmospheres decreased. However, the crystallinity and the PL properties of the annealed vacuum deposited thin film improved considerably. The CL spectra gave only green emission peaks ranging from 507 nm to 522 nm. Both the PL and CL emissions were ascribed to the 4f65d1 → 4f7 Eu2+ ion transitions. The AES elemental composition results for the undegraded and electron degraded thin films gave all the main elements in the SrAl2O4:Eu2+,Dy3+ material, i.e. Sr, Al and O. The ratios of Al and Sr APPHs to that of O increased slightly during removal of the C from the surface. The C/O ratio decreased with an increase in electron dose. Results from the RBS showed thin film SrAl2O4:Eu2+,Dy3+ stoichiometric ratios comparable to the commercial powder. The sharp decrease in the C/O APPH ratio was due to removal of C from the surface due to the electron stimulated surface chemical reactions (ESSCRs) which took place during electron bombardment. During the ESSCR process, the electron beam dissociates the O2 and other background species such as H2O to atomic species which subsequently react with C to form volatile compounds (COX, CH4, etc.). The CL intensity degraded during prolonged electron beam irradiation due to the ESSCR process. The CL degradation increased with the increase in the chamber base pressure. The XPS data collected from the degraded films proved that strontium oxide (SrO) and aluminium oxide (Al2O3) were formed on the surface of the films as a result of the ESSCR in line with the increase of Sr/O and Al/O from the AES results.
Keywords: X-ray photoelectron spectroscopy; Auger electron spectroscopy; Scanning electron microscopy; Atomic force microscopy; Cathodoluminescence; Photoluminescence; Afterglow; Thin films; Dy3+; Pulsed laser deposition; SrAl2O4:Eu2+; Thesis (Ph.D. (Physics))--University of the Free State, 2010